The Early Iron Age hoard from Jelenov klanec in Kranj - Pavlin, Primož; Turk, Peter; Urankar, Rafko; Josipovič, Draško (Arheološki vestnik, 2024)
In the summer of 1998, protective excavations were carried out during the construction of a car park on Jelenov klanec in Kranj. A hoard consisting of more than 400 bronze objects was discovered in a natural niche under a conglomerate wall: weapons, tools, jewellery, sheet metal and ingots as well as iron slag and iron ore. The objects in the hoard date from the 10th to 8th century BC, when they were probably also buried. The chemical composition of the objects from the hoard, especially the shaft-hole axes, shows relatively high proportions of lead and, in a few cases, iron in the alloy. Numerous contemporary pottery finds and two bronze pins were discovered in the settlement layers near the hoard, and the skeletal grave of a newborn was found not far away.